PREFERRED PRACTICE OF CATARACT SURGERY IN BROWN CATARACT: A QUESTIONNAIRE-BASED SURVEY - Mandal, Govind Kumar; Roy, Pummy; Choudhary, Jagdish (Student’s Journal of Health Research Africa, 2024)
Background Brown cataracts, also called brunescent or hypermature cataracts, are difficult to operate on due to their thick nuclear sclerosis, capsular issues, and poor visualization. Ophthalmic surgeons debate the best surgical method for these cases based on their training, experience, and resources. Understanding preferred surgical methods may improve uniformity and training protocols. Objective: A structured questionnaire survey of ophthalmic surgeons’ preferred brown cataract surgical methods, intraoperative approaches, and postoperative management protocols. Methods A 20-item standardized questionnaire was given to 12 ophthalmic surgeons, 6 consultants, and 6 postgraduate trainees. Demographics preferred surgical methods (phacoemulsification, MSICS, ECCE), nucleus disassembly techniques, capsular dyes and viscoelastics, perceived complication rates, and IOL implantation methods were collected in the survey. Results 58% of 12 respondents preferred MSICS for brown cataracts due to better nucleus extraction control and lower endothelial trauma risk. 33% chose phacoemulsification, mostly consultants with advanced experience and modern equipment. ECCE was used by 9% in resource-limited settings. 83% of surgeons routinely stained the anterior capsule with trypan blue, while 67% preferred dispersive viscoelastics to protect the corneal endothelium. The most common complication was posterior capsular rupture (25%), followed by zonular dialysis (16.7%). 50% used rigid PMMA lenses, but 42% preferred foldable lenses when available. Postoperative visual outcomes were satisfactory for 92% of respondents. Conclusion Ocular surgeons treating brown cataracts tend to use MSICS due to its safety, cost-effectiveness, and suitability for advanced nuclear sclerosis. Phacoemulsification is becoming more popular, but resource availability and the learning curve limit its use. Trypan blue and viscoelastics are widely used, indicating good surgical planning to reduce issues. These findings emphasize the need for MSICS and phacoemulsification training for complex cataracts and increased surgical adjunct availability in resource-limited settings.